Derivative

Calculate the second derivative of (x^7)-(x^5)+10

Hint
The power rule for the first derivative:
$$$\frac{d}{dx}[x^n]=n\cdot x^{n-1}$$$
Hint 2
Using the power rule for the first derivative, and applying it twice, we’ll get the second derivative power rule:
$$$\frac{d^2}{dx^2}[x^n]=\frac{d}{dx}\frac{d}{dx}[x^n]=\frac{d}{dx}[nx^{n-1}]=n\frac{d}{dx}[x^{n-1}]=n(n-1)(x^{n-2})$$$
Using the power rule for the first derivative, and applying it twice, we’ll get the second derivative power rule:
$$$\frac{d^2}{dx^2}[x^n]=\frac{d}{dx}\frac{d}{dx}[x^n]=\frac{d}{dx}[nx^{n-1}]=n\frac{d}{dx}[x^{n-1}]=n(n-1)(x^{n-2})$$$
This calculus problem can be written as:
$$$\frac{d^2}{dx^2}(x^7-x^5+10)=\frac{d^2}{dx^2}(x^7)-\frac{d^2}{dx^2}(x^5)+\frac{d^2}{dx^2}(10)$$$
Applying the 2nd power rule to the first section of the derivative with $$n=7$$ :
$$$\frac{d^2}{dx^2}[x^n]=n(n-1)(x^{n-2})\rightarrow\frac{d^2}{dx^2}(x^7)=42x^5$$$
Applying the 2nd power rule to the second section of the derivative with $$n=5$$ :
$$$\frac{d^2}{dx^2}[x^n]=n(n-1)(x^{n-2})\rightarrow\frac{d^2}{dx^2}(x^5)=20x^3$$$
Applying the constant rule to the third section of the derivative:
$$$\frac{d^2}{dx^2}[10x^0]=0$$$
Finally,
$$$\frac{d^{2}}{dx^{2}}(x^{7})-\frac{d^{2}}{dx^{2}}(x^{5})+\frac{d^{2}}{dx^{2}}(10)=42x^5-20x^3$$$
$$$42x^5-20x^3$$$